Kesalahan Afiksasi dalam Caption Instagram @Infojember Edisi Oktober 2022 - Alfi Khoiru An Nisa; Novi Auliana Putri; Imam Baehaqie; Rustono (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to describe affixation errors in the October 2022 edition of the Instagram @infojember social media caption. Qualitative research is the type of this research that uses a descriptive approach. The October 2022 edition of Instagram @infojember social media is the research data source. The data was used in the form of affixation errors that exist in the October 2022 edition of the @infojember caption. The reading and note-taking techniques were used in this research, namely by reading each caption critically; then, if it saw symptoms of affixation errors, it was recorded and grouped according to the indicators that had been made previously. The data analysis techniques by reducing data, presenting data, and drawing conclusions. The study's results found that there are still affixation errors in the October 2022 edition of Instagram @infojember social media, namely 15 errors, with details of 7 errors in prefix errors, 3 errors in suffix errors, and 5 errors in confix errors. The data found have the same types of errors, namely in the form of prefix omission, suffix omission, and confix omission.